ANALISIS PENGENDALIAN PERSEDIAAN MODUL ABS (ANTI-LOCK BRAKING SYSTEM) MENGGUNAKAN METODE CONTINUOUS REVIEW (Q) DAN PERIODIC REVIEW (P) PADA PT. XYZ (INDUSTRI OTOMOTIF) - Khansa Ghina Aullia (2022)
PT. XYZ is a company engaged in the automotive industry, especially in the manufacture of cars. In the manufacture of cars there is a problem, namely the difference between production planning and actual production caused by a shortage of ABS (Anti-lock Braking System) module inventory. The purpose of this study is to analyze inventory control of the ABS (Anti-Lock Braking System) module using the Continuous Review System (Q) and Periodic Review System (P) methods to prevent excess or shortage of inventory. Based on inventory control calculations, the continuous review system (Q) method with back order is the best method because it has the smallest total inventory cost of Rp.26,009,481,635 compared to other inventory methods and company methods. By using the continuous review system (Q) back order method, the number of orders (q) is 3657 units, reorder point (r) is 2743 units, safety stock is 364 units and the company can save inventory costs of Rp. 41,993,223.